Coolidge effect in pond snails: male motivation in a simultaneous hermaphrodite - Koene, Joris M (BioMed Central, 2007)
BACKGROUND: The simultaneously hermaphroditic pond snail, Lymnaea stagnalis, can mate in the male and female role, but within one copulation only one sexual role is performed at a time. Previous work has shown that male motivation is determined by the availability of seminal fluid in the prostate gland, which is detected via a nervous connection by the brain area controlling male behaviour. Based on this knowledge, patterns of sexual role alternations within mating pairs can be explained. RESULTS: The data presented here reveal that these snails can donate and receive sperm several times within 24 hours, and that they have increased mating rates in larger groups (i.e. more mating opportunities). For mating pairs we show, by introducing novel mating partners after copulation, that animals do inseminate new partners, while they are no longer motivated to inseminate their original partners. CONCLUSION: Our findings provide the first direct evidence for higher motivation in a hermaphrodite to copulate when a new partner is encountered. This Coolidge effect seems to be attenuated when mucus trails are excluded, which suggests that a chemical or textural cue may be responsible for mediating this response to sperm competition.